Type specimens of vascular plants in the herbarium of the National Institute of Biological Resources (II) - Jang, Hyun-Do; Hyun, Chang-Woo; Ryu, Seah; Lee, Sang-Jun (Phytotaxa, 2022)
We provide information on 143 sheets of type specimens of 39 species and infraspecific taxa of vascular plants stored in the herbarium of the National Institute of Biological Resources. The specimens were donated by Changwon National University (Prof. Hyeok-Jae Choi), Chungbuk National University (Prof. Byoung-Un Oh), Ewha Womans University (Prof. Chang-Sook Lee), Hallym University (Prof. Young-Dong Kim), Jeonbuk National University (Prof. Muyeol Kim), Korea National Arboretum, Mokwon University (Prof. Jeong Ki Sim), Sungkyunkwan University (Prof. Seung-Chul Kim), and some researchers at KB. The specimens included four sheets for holotypes, 46 sheets for isotypes, and 93 sheets for paratypes of three species and infraspecific taxa of pteridophytes, 21 dicotyledons, and 15 monocotyledons. Nine sheets were sourced from China and 134 sheets were sourced from Korea.